The development of a local government in Poland and the challenges of civilization transformations - Andrzej Chudobski (Civitas Hominibus)
The study presents that a local government is as a decentralising reality, opposite of the globalisation processes. In the realisation of a local government, an important role is played by the political and construction of citizenship processes. In shaping the face of a local government in Poland, a force of tradition and post-modernisation value collide (including negating heritage of the past, the authority of the people of a cultural life). The process of political and economic transition reveal trends to getting acquainted with foreign designs (Anglo-Saxon) of a cultural life; in this situation, localism becomes a particular value. The level of development of a local government is a measure of the socio-political life, including its democracy.